Service of rapid magnetic variations, an update. Issue 1 (17th June 2022) - Curto, Juan José; Segarra, Antoni; Altadill, David; Chambodut, Aude
Abstract: Rapid magnetic variations on Earth are intimately linked with solar activity and this is one of the main topics in Space Weather research. Modelling and forecasting these phenomena are vital in our technological society. The Service of Rapid Magnetic Variations provides lists of these remarkable magnetic events in a continuous way in what constitutes a long geophysical series that began in the late 19th century. Although the aim of this Service remains unchanged, methods have changed with time. Here, we describe the recent evolution of the Service, its database and the latest works carried out to improve the products delivered to the scientific society. Abstract : Map with the five low‐latitude observatories used to determine sudden commencements (SC) amplitude. Green dots represent the location of the original ones. Red squares represent the location of the observatories used currently. Blue triangles are those used as alternative to the main ones when their magnetograms are not available.